2003
DOI: 10.1103/physreve.67.060104
|View full text |Cite
|
Sign up to set email alerts
|

Reaction-diffusion dynamics: Confrontation between theory and experiment in a microfluidic reactor

Abstract: We confront, quantitatively, the theoretical description of the reaction-diffusion process of a second-order reaction to experiment. The reaction at work is Ca(2+)/CaGreen, a fluorescent tracer for calcium. The reactor is a T-shaped microchannel, 10 microm deep, 200 microm wide, and 2 cm long. The experimental measurements are compared with the two-dimensional numerical simulation of the reaction-diffusion equations. We find good agreement between theory and experiment. From this study, one may propose a metho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(81 citation statements)
references
References 9 publications
1
79
0
1
Order By: Relevance
“…Several experimental works in gels have validated these RD scalings using A þ B-C types of reaction, see Koo et al (1990), Taitelbaum et al (1992) and Yen et al (1996), like for instance the complexation reaction of Cu 2 þ with a substrate studied by Koo and Kopelman (1991) in an agarose gel. More recently, a different type of convection-free experiment carried out by Baroud et al (2003) in a T-shaped microfluidic reactor has further confirmed these RD scalings using the binding reaction of Ca 2 þ with calcium green. All these experiments are not only in excellent agreement with the theoretical scalings, but the actual positions of the reaction front are very close to the predicted theoretical values.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…Several experimental works in gels have validated these RD scalings using A þ B-C types of reaction, see Koo et al (1990), Taitelbaum et al (1992) and Yen et al (1996), like for instance the complexation reaction of Cu 2 þ with a substrate studied by Koo and Kopelman (1991) in an agarose gel. More recently, a different type of convection-free experiment carried out by Baroud et al (2003) in a T-shaped microfluidic reactor has further confirmed these RD scalings using the binding reaction of Ca 2 þ with calcium green. All these experiments are not only in excellent agreement with the theoretical scalings, but the actual positions of the reaction front are very close to the predicted theoretical values.…”
Section: Introductionmentioning
confidence: 58%
“…The various chemical reactions that have been used to verify the RD scalings predicted by G alfi and Racz (1988) could be used to compare with our theoretical results. These reactions have kinetic constants ranging between k $ 10 À1 and $ 10 6 M À1 s À1 , see Baroud et al (2003), Koo and Kopelman (1991) and Taitelbaum et al (1992), which, along with the initial reactant concentration a 0 between 5:0 Â 10 À5 M and 1:0 Â 10 À3 M, gives characteristic times t c ¼ 1=ðka o Þ varying between t c ¼ 10 À3 s and t c ¼ 2 Â 10 5 . The diffusion coefficients of the involved species are equal to D $ 3:028:0 Â 10 À6 cm 2 =s, see Baroud et al (2003), Koo and Kopelman (1991) and Taitelbaum et al (1992), corresponding to characteristic length scales L c ¼ ffiffiffiffiffiffiffiffi Dt c p running between 5:5 Â 10 À4 mm and 1:2 cm.…”
Section: Experimental Values Of Physical Parametersmentioning
confidence: 99%
“…how the reaction product, C, turns into precipitate). While the front properties have been thoroughly studied and understood both theoretically [17,18] and experimentally [19,20], the dynamics of precipitation is more debated [13,18]. The competing pre-and post-nucleation views can be combined [18,21], and we shall use a simple version [14] based on the Cahn-Hilliard equation with noise added [22][23][24].…”
mentioning
confidence: 99%
“…5,[28][29][30][31] In particular they can be used to measure reaction rates that would otherwise be impossible using conventional stopped-flow techniques. 5 Fluorescence lifetime images were acquired at 0, 1, 2.5 and 10 mm from the point of confluence (corresponding to average residence times of 108, 540, 1350 and 5400 ms) using multiphoton FLIM microscopy and resulting fluorescence decay profiles were fitted to a single exponential decay model ( Figure 2). As expected, the extracted decay times increase as the two species diffuse and bind near the center of the microchannel.…”
Section: Resultsmentioning
confidence: 99%